Social representations of sex and gender among trans people - Jaime Alonso Caravaca Morera; Maria Itayra Padilha
ABSTRACT Objective: To analyze the social representations of sex and gender among transsexual people, through their life histories. Method: Qualitative, multicenter and descriptive research. The participants were 70 transsexuals from Brazil and Costa Rica. Data were analyzed according to the technique of Content Analysis. Results: Two complementary representations related to sex were identified: "Sex as a natural categorical imposition sealed and acquired (irremediably) at birth" and "Sex as an element that labels, condemns and differentiates people." Regarding gender, a single representation was associated with "synthetic-social constructions associated with (necro/bio) power, cisnormativity and culture." Final considerations: The former absolute division of gender as social construction and of sex as considered as natural must be questioned in order to analyze both concepts as an interconnected dyad. In addition, it should be recognized that this dyad presents itself as an organizational and cognitive construct, mediated by the still prevalent cispatriarchal (necro/bio) power.